Transact-SQL programming - Kline, Kevin E. 1966-; Gould, Lee; Zanevsky, Andrew (O'Reilly, 1999)
Provides detailed information about Transact-SQL programming and shows specific differences between the Microsoft and Sybase versions of the language.
Systemvoraussetzungen: Microsoft SQL Server 6.5/7.0 & Sybase Adaptive Server 11.5; CD-ROM-Laufwerk
Keywords: Podatkovne baze - Priročniki; SQL (programski jezik) - Priročniki; SQL strežnik - Priročniki; Transact SQL; CD-ROM